TANFĪDZU AL-THARĪQAH AL-INTIQĀĪYATI FĪ TA’LĪMI AL-LUGAH AL-ARABĪYATI LADĀ AL-TULLĀBI FĪ AL-SHIFFI AL-HĀDĪ ‘ASYARA BI AL-MADRASATI AL-ṮSĀNAWĪYATI NŪRUL AL-HIKAM SITUBONDO LIL SANATI AL-DIRĀSĪYATI 2022/2023 M. - Iliyati, Sayyidatina; Aulia Ainy, Cindy (Critical Review of English-Arabic World Journal, 2023)
Nurul Hakam Situbondo Secondary School is one of the schools located in the village of Kaspera, which is dedicated to teaching the Arabic language. Its teaching has problems, such as the efficiency of teaching the Arabic language in this school is low and the desire of the students to study the Arabic language is incomplete. During the observation, the researcher found several things, namely lack of interest in learning due to monotonous learning, suboptimal student potential due to unavailability of learning media, different student characteristics, and school environment factors that are less supportive in the teaching and learning process. The researcher chooses the place of research in Nour Al-Hakam Secondary School, which: First, there was no accustomed to using the two languages ​​in daily life, and second, in this school the eclectic method was used in teaching the Arabic language. The objectives of the research are: describing the implementation and evaluation of the eclectic method in teaching the Arabic language to students in the eleventh grade of Nurul Hakam Situbondo Secondary School for the academic year 2022/2023 AD. The research method that the researcher used is descriptive qualitative approach research with the method of collecting data, which is observation and personal interview. And documentary. This research uses the technique of validity of the research, source triangulation and triangulation technique The results of the research are the implementation of the selective method in teaching the Arabic language to students in the eleventh grade of Nour Al-Hakam Secondary School. The lesson says peace to the students, then he asks them about the news and asks the students who did not enter the class. Then the teacher ordered the students to close the Arabic language lesson book and then asked them about the lesson learned yesterday. After that, the teacher explained the educational material clearly, then the teacher gave all students the opportunity to choose and write one incomprehensible vocabulary on the board, after the students had written all the vocabulary. The teacher read the vocabulary words with their meaning one by one and took turns with the students. Then in conclusion, the teacher evaluated and evaluated the students in each meeting.